Produção de isoprenóides e estratégias de alocação de recursos em espécies arbóreas da Amazônia central - Rezende, Michelle Robin Carneiro de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
Isoprenoids are secondary organic compounds characterized mainly by isoprene, monoterpenes and sesquiterpenes. Isoprene and constitutive monoterpenes are compounds that possibly mitigate heat and oxidative stress in leaves, but monoterpene production demands more carbon. Storable monoterpenes and sesquiterpenes can provide an induced protection from herbivory attack and pathogens, yet production is even more costly. This relationship between possible benefits and the associated carbon costs of isoprenoid production could characterize an important ecological trade-off, and present the opportunity to assess this production through plant economic strategies. Here we investigate the relationship between isoprenoid emission and storage with functional traits of leaf, wood and whole-plant economic spectra, for 27 tree species in central Amazon. Investments in emissions of isoprene and monoterpenes were more associated to leaf traits. From species with a fast leaf strategy to species with slow leaves, there was a shift from a less costly isoprene production to a more expensive monoterpene one. However, the capacity to emit isoprene seems to modulate the coordination between economic spectra of different plant levels. Species that did not emit isoprene tended to exhibit the same economic strategy for leaf, wood and whole-plant; while isoprene emitters presented opposite strategies (e.g. fast leaves and slow wood/whole-plant traits). The storage of monoterpenes and sesquiterpenes was associated with wood and whole-plant traits. Species with fast wood and whole-plant traits showed leaf storage of monoterpenes and sesquiterpenes. Through this study it was possible to conclude that the carbon economic spectra of plant strategies coordinate with emission and storage of isoprenoids. Such results can contribute to integrating these secondary compounds within plant functional strategy studies, as well as to a deeper ecological understanding of isoprenoid production mechanisms, which could possibly contribute to more accurate global flux estimates.
Leaf, wood and whole-plant economic spectra coordinate with isoprenoid emission and storage in central Amazon trees
Keywords: Compostos secundários; Traços funcionais; Estratégias de plantas; Isopreno; COVBs; Floresta Amazônica